Headache as First Symptom of Cerebral Tumor - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Five children, ranging in age from 10 months to 4 years, all presenting initially with headache, with or without vomiting, and in whom the final diagnosis was intracranial tumor, are reported from Petah Tiqva, Israel.